O desenho infantil como instrumento mediador na construção dos conceitos científicos no ensino de ciências naturais - Antunes, Rafael Felipe Sousa (2019)
Since child, while students, we have been prepared to at some moment of our lives carry out a test or even an exam. With the character of an educational tool, tests and/or exams have been widely applied for the purpose of evaluating and measuring what has been “learned” by the student, however, they are not the only educational tool available to assess or measure the knowledge acquired by the student. In this context, the children’s drawing, which has long been trivialized, being it in the application for the purpose of relaxation or technical nature (mimeographed and ready-to-color drawings), presents itself as an interesting educational tool to identify what has been internalized by the child, thus being linked to child learning and development. Children’s drawing assumes a multidisciplinary position, while interacting with various branches of knowledge, either in a dialectical and dialogical process, establishing an intercommunication, at the same time, with the environment in which it is produced, with the context to which it refers, and with the individuals involved in the design and reception process, either directly or indirectly. Nowadays we are faced with a great fragmentation of knowledge, thus children’s drawing present itself as a versatile tool when used in the correct way, being able to be used in an interdisciplinary way. Mainly based on L. S. Vygotsky this research aimed to highlight the importance of children’s drawing as a methodological and educational tool for teaching-learning in the teaching of Natural Sciences, specially in the development of scientific concepts related to nature, as well as stimulating the children’s imagination by putting focus its perception on creating and re-creating its drawings. The methodology proposed here aims to place the child in a prominent place, being it the protagonist of what creates. Field classes, along with the presentation of stuffed animals, aimed to intensify the lived experienced by the children, so that this experience marks them in some way, being able or not to reflect in the realized drawings. The results suggest the children’s drawing linked to other practices is a useful and versatile instrument, breaking paradigms that the only ways of evaluation are in tests/exams. We propose, then, that drawing be used as a common language, not as mere amusement, but as a useful instrument, useful in its many forms, so that when the child draws, it brings to the paper in form of art, mental images and creates its work thus having a dialectical relationship between what imagines and what draws, leaving recorded in its work what he/she is feeling, what he/she thinks, or what he/she would wish to happen, passing between past, present and future. Thus, we argue here that drawing should not be taken only as an end, but as a means, the purpose of which is to learn to see, to discover, to preserve, to remember, to reproduce, to create, and above all, the purpose of instructing and teaching.